2015
DOI: 10.1371/journal.pone.0120356
|View full text |Cite|
|
Sign up to set email alerts
|

Binge Ethanol Prior to Traumatic Brain Injury Worsens Sensorimotor Functional Recovery in Rats

Abstract: A significant number of patients suffering from traumatic brain injury (TBI) have a high blood alcohol level at the time of injury. Furthermore, drinking alcohol in a binge-like pattern is now recognized as a national problem, leading to a greater likelihood of being injured. Our objective was to determine the consequences of a binge paradigm of alcohol intoxication at the time of TBI on long-term functional outcome using a sensitive test of sensorimotor function. We trained adult, male, Sprague Dawley rats on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
5
21
0
Order By: Relevance
“…The mean BAL at the time of TBI was 156.1 mg/dl ± 8.3 mg/dl. This level is consistent with previous reports using the same animal strain, (Livy, Parnell, & West, ; Vaagenes et al, ) and is approximately twice the legal intoxication limit in humans (Olthuis et al, ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The mean BAL at the time of TBI was 156.1 mg/dl ± 8.3 mg/dl. This level is consistent with previous reports using the same animal strain, (Livy, Parnell, & West, ; Vaagenes et al, ) and is approximately twice the legal intoxication limit in humans (Olthuis et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Our group has shown that in a rat model of TBI and binge alcohol, recovery in a skilled sensorimotor task was slower and the recovery plateau was lower in alcohol-exposed animals (Vaagenes et al, 2015) as also reported in clinical studies (Corrigan, 1995;Gurney et al, 1992;Joseph et al, 2015;Schutte & Hanks, 2010) although others have found a benefit (Chandrasekar et al, 2018(Chandrasekar et al, , 2017Lundgaard et al, 2018).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Additionally, weekend binge drinking is a pattern observed in many cultures (Lundqvist, Alling, Knoth, & Volk, 1995). To mirror this drinking pattern, our laboratory used a mouse model of episodic binge ethanol intoxication prior to burn injury (adapted from (Callaci et al, 2004), (Przybycien-Szymanska, Mott, & Pak, 2011; Przybycien-Szymanska, Rao, & Pak, 2010; Qin et al, 2014; Vaagenes et al, 2015)) to assess respiratory physiology and gain an understanding of the effect of intoxication on lung function after burn injury.…”
Section: Introductionmentioning
confidence: 99%